2006
DOI: 10.1111/j.1365-2249.2006.03218.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against CD28 are associated with atopic diseases

Abstract: SummaryThe B7-1/B7-2-CD28/CTLA-4 pathway is crucial in regulating T cell activation and tolerance. Autoantibodies to surface molecules on lymphocytes have already been described in various immune conditions, such as autoimmune diseases, infections and blood transfusions. The objective of this study was to test sera from healthy individuals and from patients for association of CD28 autoantibodies with inflammatory and non-inflammatory diseases. First, CD28 was obtained by digestion of CD28-Ig fusion protein wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…It is also known that autoantibody against α-enolase is involved in autoimmune disease [19]. Many previous studies have shown that sera of patients with severe AD contain autoantibody specific for self-proteins, supporting the hypothesis of autoreactivity as a pathogenic factor in AD [20, 21]. Thus, it also seems possible that α-enolase is involved in the pathogenesis of AD as an autoreactive factor.…”
Section: Discussionmentioning
confidence: 94%
“…It is also known that autoantibody against α-enolase is involved in autoimmune disease [19]. Many previous studies have shown that sera of patients with severe AD contain autoantibody specific for self-proteins, supporting the hypothesis of autoreactivity as a pathogenic factor in AD [20, 21]. Thus, it also seems possible that α-enolase is involved in the pathogenesis of AD as an autoreactive factor.…”
Section: Discussionmentioning
confidence: 94%
“…In addition to immunologic sensitization to chemicals, both intrinsic asthma (Nahm et al 2002) and asthma caused by diisocyanate exposure are associated with antibodies directed to epithelial components (Ye et al 2006a). Other autoantibodies in asthma include those directed to heatshock protein (HSP)-70 (Yang et al 2005), CD28 (Neuber et al 2006), and a-enolase (Nahm et al 2006). Whether such autoantibodies are truly pathogenetic or related more to tissue damage and inflammation remains to be established (Ye et al 2006b).…”
Section: Nonallergic (Late-onset or Intrinsic) Asthmamentioning
confidence: 99%
“…19 Autoantibodies against CD28 were found stimulate T cells and overcome the CD152-Ig-induced anergy of T cells in an mixed lymphocyte reaction. 20 The function of autoantibodied to CD80 need to be clarified.…”
Section: Discussionmentioning
confidence: 99%